Association of increased renal Cyp24a1 gene expression with low plasma 1,25-dihydroxyvitamin D levels in rats with streptozotocin-induced diabetes - Tajiri, Mari (J Clin Biochem Nutr, 2020)
Decreases in plasma vitamin D concentrations have been reported in diabetes, although the mechanism involved in this decrease is unclear. Here, we investigated the association between Cyp24a1, a vitamin D catabolic enzyme, and abnormalities in vitamin D metabolism in streptozotocin-induced diabetes rats, an animal model of type 1 diabetes. Plasma 1,25-dihydroxyvitamin D [1,25(OH)(2)D] levels were significantly lower in streptozotocin-induced diabetes rats and renal Cyp24a1 mRNA expression levels were increased. Western blotting analysis of streptozotocin-induced diabetes rats kidney tissues with anti-CYP24A1 antibody showed a strong signal around 40 kDa, which differs from the predicted 50–55 kDa molecular weight for full-length Cyp24a1 and could represent the Cyp24a1-splicing variant that lacks exons 1 and 2. We observed high levels of renal Cyp24a1-splicing variant mRNA expression in streptozotocin-induced diabetes rats. We also confirmed transcriptional up-regulation of endogenous Cyp24a1 mRNA expression through glucocorticoid receptors by glucocorticoid in opossum kidney proximal cells. Taken together, our results indicated that high Cyp24a1 expression levels may play a role in the decrease of plasma 1,25(OH)(2)D levels in streptozotocin-induced diabetes rats. High plasma corticosterone levels in diabetes may affect transcriptional regulation to promote increases in Cyp24a1 expression.